Superoxide production by NAD(P)H oxidase in human blood vessels: Functional interaction with nitric oxide - Guzik, T; West, N; Black, E; McDonald, D; Ratnatunga, C; Pillai, R; Channon, K (2000)
Increased superoxide (SO) production in animal models of vascular disease contributes to reduced nitric oxide (NO) activity, endothelial dysfunction and oxidative stress. However, the importance of SO production in human atherosclerosis is poorly characterised. We aimed to determine the sources of SO in human blood vessels, and study NO-SO interactions. Methods: We studied basal and NADH-stimulated SO production using lucigenin-enhanced chemiluminescence); NO-dependent vasorclaxations (as a bioassay of NO production) and immunoblotting for NAD(P)H oxidase protein subunits p22phox and p67phox in human saphenous veins (HSV) and internal mammary rteries (IMA). Results: SO production, observed in all HSV (n=110) and IMA (n=25), was inhibited by 80% by diphenylene iodinium, stimulated by NADH and NADPH, and localised to cell membranes after subcellular fractionation, all characteristic features of the NAD(P)H oxidase system. Immunblotting demonstrated p22phox and p67phox proteins in HSV: protein densitometry revealed a correlation between p67phox protein levels and NAD(P)H oxidase actvity in individual patients (R=0.89; p<0.02). One third of NAD(P)H oxidase activity was present in the endothelium. Inhibition of NO synthesis significantly increased SO release (from 132 ± 11 to 201± 40 RLU/sec/mg dw; p<0.05), and NADH stimulation of vascular rings significantly decreased NO-dependent relaxation (n=21: 21.± 4.9 vs. 15.5 ± 3.2 %, p<0.01) that was restored by superoxide dismutase, demonstrating a SO-NO functional interaction. Conclusions: NAD(P)H oxidase is the principal source of SO production in human blood vessels, and may contribute to reduced NO bioavailability in human atherosclerosis.